ANALISIS PENGARUH HEAT TREATMENT 900C BAJA ST40 PADA BODY TRUK UNIMOG MILITER TERHADAP SIFAT FISIS DAN MEKANIS - Harjanto, Budi; Lumintang, D.Ricky; Sukahar (PPM Sdirjianbang Akademi Militer, 2024)
TNI-AD is an army unit whose mobility is mostly in the mainland area. In mengkaver all regions of Indonesia, requires a vehicle that is able to cross all terrain both flat terrain, and bumpy terrain that is difficult to pass by ordinary vehicles. As well as being able to transport personnel with a high level of mobility in the field of operation, so it requires a truck that is tough enough to overcome it. No less important is also the ability of the body of the truck, so that in transporting personnel and logistics must be strong and use materials made of armored are. This study aims to analyze and test the material from the content of the type of steel used in the truck body Unimog on physical and mechanical properties, when heat treated with a certain temperature.Steel type ST40 steel coating on military Unimog trucks has high hardness, can be seen from the results of hardness tests and tensile tests carried out in this experiment. The steel is broken when the steel is pulled with a strength of 5910 kg after undergoing a heat treatment process without being welded. Then the steel is broken when the steel is pulled with a strength of 4360 kg after undergoing a welded heat treatment process. Pure steel containing carbon content below 1% is a type of high quality steel, so it is suitable for use as a steel coating on the body of military vehicles.